2021
DOI: 10.4236/blr.2021.122029
|View full text |Cite
|
Sign up to set email alerts
|

Towards Maintaining Peacefulness of the Sea: Legal Regime Governing Maritime Safety and Security in Nigeria

Abstract: This study examined the development of international and municipal laws on maritime safety and security and identified the challenges undermining the efficiency of the provisions at combating security threats within the Nigerian maritime space. The study relied on primary and secondary sources of information. The primary sources included the United Nations Convention on the Law of the Sea (UNCLOS) 1982, Convention for the Suppression of Unlawful Acts against the Safety of Maritime Navigation 1988, the Safety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…Findings by MSP (2017) focusing on international and regional policy environment in the Gulf of Guinea showed that adoption of Sustainable Development Goals 16 focusing on peace, justice, strong institutions, and partnerships could ensure improved maritime security governance, which is similar to the recommended strategies in this study by implications. Similarly, a study by Babatunde and Abdulsalam (2021) focused on the development of international as well as municipal laws on maritime safety as well as security, which is related to the focus of this study. The findings by the authors showed that functional, legal, institutional and policy measures for tackling maritime insecurity in Nigeria would mitigate the challenge posed by maritime criminality in the country, which is largely related to the findings from this study.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Findings by MSP (2017) focusing on international and regional policy environment in the Gulf of Guinea showed that adoption of Sustainable Development Goals 16 focusing on peace, justice, strong institutions, and partnerships could ensure improved maritime security governance, which is similar to the recommended strategies in this study by implications. Similarly, a study by Babatunde and Abdulsalam (2021) focused on the development of international as well as municipal laws on maritime safety as well as security, which is related to the focus of this study. The findings by the authors showed that functional, legal, institutional and policy measures for tackling maritime insecurity in Nigeria would mitigate the challenge posed by maritime criminality in the country, which is largely related to the findings from this study.…”
Section: Discussion Of Findingsmentioning
confidence: 99%